2019
DOI: 10.1029/2019ea000620
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Aerosol and Boundary Layer Height in Summer in China Under Different Thermodynamic Conditions

Abstract: The observed relationships between boundary layer height (BLH) and PM2.5 on a national scale remain unclear due to the dearth of observations. Here we investigated this relationship from a unique perspective of thermodynamic stability in the planetary boundary layer (PBL), using summertime (June–August) soundings from China for the period from 2014 to 2017. For all three times of soundings (0800, 1400, and 2000 Beijing time [BJT]), positive (negative) PM2.5 concentrations anomalies were found to correlate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 63 publications
4
34
1
Order By: Relevance
“…This reduced radiation, in turn, reduces turbulence generation and hence the PBLH. The humidity values are found to be higher during the periods of higher AOD, which support the availability of more latent heat for the convection growth (Lou et al, 2019). For the present study, a negative BLH anomaly is found within and close to the domain, especially on the event day (see Figure 3).…”
Section: Resultssupporting
confidence: 80%
“…This reduced radiation, in turn, reduces turbulence generation and hence the PBLH. The humidity values are found to be higher during the periods of higher AOD, which support the availability of more latent heat for the convection growth (Lou et al, 2019). For the present study, a negative BLH anomaly is found within and close to the domain, especially on the event day (see Figure 3).…”
Section: Resultssupporting
confidence: 80%
“…DGSR is also crucial for the utilization of solar energy through transformation of technologies (Wu et al, 2012(Wu et al, , 2016Tang et al, 2018;Prăvălie et al, 2019;Zou et al, 2019). In recent years, there has been an aggravation of air pollution in China induced by massive fossil fuel consumption and emissions coinciding with unfavorable weather conditions (Guo et al, 2016Lou et al, 2019;Yang, et al, 2018;Yang, Ye, et al, 2019;Zheng et al, 2019). On the one hand, this has significantly modulated the change in surface solar radiation (Che et al, 2005;Guo et al, 2018;Wang et al, 2012Wang et al, , 2013Wang & Wild, 2016;Zheng et al, 2018;He & Wang, 2020;Yang et al, 2020), while on the other hand, it has led to solar radiation becoming one of the fastest-growing and important sources of clean and renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the meteorology, including the planetary boundary layer (PBL), temperature, pressure, relative humidity, wind speed, wind direction, and precipitation, also exerts strong impacts on the PM 2.5 mass concentration (Chen et al, ; Garrett et al, ; Guo et al, ; He & Lin, ; He, Lin & Liu, ; Li, Feng, et al, ; Li, Guo, et al, ; Lou et al, ; Pearce et al, ). The variation of PBL height governs the concentrations of atmospheric pollutants near the surface since the aerosol particles generally concentrate within the PBL height (Garratt, ; Guo et al, ; Seidel et al, ).…”
Section: Introductionmentioning
confidence: 99%